Pengetahuan dan sikap ibu hamil terhadap penggunaan alat USG (USG) dalam pemeriksaan antenatal care (ANC) di Desa Waung Kecamatan Boyolangu Kabupaten Tulungagung - maryam; Anindya Ervianti (JURNAL KEBIDANAN, 2023)
ABSTRACT Background : Pregnancy health service programs can be monitored through antenatal care examinations in accordance with service standards, namely a minimum of 6 examinations during pregnancy and a minimum of 2 examinations by a doctor in the first and third trimesters, one of which is an ultrasound examination, as well as 1 midwife examination in the first trimester, 1 time in the second trimester and twice in the third trimester. ANC examinations must be carried out periodically to see progress and identify risk factors in pregnant women early so that pregnancy, childbirth and postpartum can be carried out well. However, in reality, not all pregnant women make ANC visits due to mothers' lack of knowledge about the importance of ANC examinations. The aim is to identify the knowledge and attitudes of pregnant women towards the use of ultrasound (USG) in antenatal care (ANC) examinations in Waung Village, Boyolangu District, Tulungagung Regency.. Method : The design uses descriptive. The population of all pregnant women acceptors was 40. Based on purposive sampling, the sample size was 36 respondents. The research was conducted from 26 December 2022 to 21 January 2023 in Waung village, Tulungagung Regency. Results : it was obtained from 36 respondents that the majority of respondents (64%) or 23 respondents had sufficient knowledge and a small part of respondents (8%) or 3 respondents had insufficient knowledge. And most of the respondents (56%) or 20 respondents had a positive attitude about the use of ultrasound (USG) in antenatal care (ANC) examinations and almost half of the respondents (44%) or 16 respondents had a negative attitude about the use of ultrasound (USG). at antenatal care (ANC) screeningEnglish literacy were statistically significant (p < 0.001). It was also found that the group of students using English literacy increased student research development with an effect value (ES = 7.60) compared to the group of students who did not use English literacy. Conclution : it was concluded that respondents with fairly good knowledge would produce or be able to respond positively to problems regarding the use of ultrasound (USG) in antenatal care (ANC) examinations, and vice versa if respondents with insufficient knowledge would respond to these problems unfavorably or negatively.